A Preprocedural Checklist Improves the Safety of Emergency Department Intubation of Trauma Patients. (20th July 2015) - Smith, Kurt A.; High, Kevin; Collins, Sean P.; Self, Wesley H.; Reardon, Robert
Abstract Objectives Endotracheal intubation of trauma patients is a vital and high‐risk procedure in the emergency department (ED). The hypothesis was that implementation of a standardized, preprocedural checklist would improve the safety of this procedure. Methods A preprocedural intubation checklist was developed and then implemented in a prospective pre‐/postinterventional study in an academic trauma center ED. The proportions of trauma patients older than 16 years who experienced intubation‐related complications during the 6 months before checklist implementation and 6 months after implementation were compared. Intubation‐related complications included oxygen desaturation, emesis, esophageal intubation, hypotension, and cardiac arrest. Additional outcomes included time from paralysis to intubation and adherence to safety process measures. Results During the study, 141 trauma patients were intubated, including 76 in the prechecklist period and 65 in the postchecklist period. A lower proportion of patients experienced intubation‐related complications in the postchecklist period (1.5%) than the prechecklist period (9.2%), representing a 7.7% (95% confidence interval = 0.5% to 14.8%) absolute risk reduction. Paralysis‐to‐intubation time was also lower in the postchecklist period (median = 82 seconds, interquartile range [IQR] = 68 to 101 seconds) compared to the prechecklist period (median = 94 seconds, IQR = 78 to 115 seconds; p = 0.02). Adherence to safety process measures also improved, with all safety measures performed in 69.2% in the postchecklist period compared to 17.1% before the checklist (p < 0.01). Conclusions Implementation of a preintubation checklist for ED intubation of trauma patients was associated with a reduction in intubation‐related complications, decreased paralysis‐to‐intubation time, and improved adherence to recognized safety measures.